1975
DOI: 10.1002/macp.1975.021760411
|View full text |Cite
|
Sign up to set email alerts
|

The photolysis of copolymers of methyl methacrylate and methyl acrylate

Abstract: The photolysis of copolymers of methyl acrylate and methyl methacrylate, covering the entire composition range, is studied with the copolymers in the form of film and in solution, under vacuum and in an atmosphere of oxygen. In film under vacuum, copolymers with high acrylate contents become insoluble, and cross‐linking and chain scission may be separated by application of the Charlesby‐Pinner equation to sol‐gel separation data. Otherwise, the polymer remains soluble, chain scission predominates and may be me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…In agreement with the literature data for acrylic resins,1, 2 the infrared and second derivative spectra of the Paraloid and their blends with Tecnoflon showed variations after this treatment at level of the aliphatic CH stretching vibrations between 3000 and 2800 cm −1 , of the –C–O–C modes (1330–900 cm −1 ) and the CO stretching vibration in the 1750–1680 cm −1 region (Figs 3 and 4).…”
Section: Uv Radiation Effectssupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with the literature data for acrylic resins,1, 2 the infrared and second derivative spectra of the Paraloid and their blends with Tecnoflon showed variations after this treatment at level of the aliphatic CH stretching vibrations between 3000 and 2800 cm −1 , of the –C–O–C modes (1330–900 cm −1 ) and the CO stretching vibration in the 1750–1680 cm −1 region (Figs 3 and 4).…”
Section: Uv Radiation Effectssupporting
confidence: 91%
“…Previous research has shown that acrylic resins and other similar compounds deteriorate over time particularly under conditions of UV radiation 1–3. Nowadays their use as protective agents for stones is therefore limited.…”
Section: Introductionmentioning
confidence: 99%
“…8 The effect is rather signicant under the illumination of short UV wavelength. This hypothesis was proven true in many case studies involving homopolymer and similar trends were reported for copolymers such as poly(methyl methacrylateco-methyl acrylate) P[MMA-co-MA] 9 and poly(vinyl acetate-cobutyl acrylate) P[VA-co-BA].…”
Section: Introductionmentioning
confidence: 59%